Receptor-Heteromer Investigation Technology and its application using BRET - Pfleger, Kevin; Johnstone, Elizabeth K. (Frontiers in Endocrinology, 2012)
Receptor heteromerisation has the potential to alter every facet of receptor functioning, leading to new pharmacological profiles with increased signalling diversity and regulation from that of the monomeric receptor, or indeed receptor homomer. An understanding of the molecular consequences of receptor heteromerisation will provide new insights into the physiology and pathology mediated by receptors, expanding the possibilities for pharmacological discovery. Particularly advantageous approaches to investigate novel heteromer pharmacology utilise cell-based assay technologies that assess ligand-dependent functional responses specific to the receptor heteromer. Importantly, this allows for differentiation of heteromer-specific pharmacology from pharmacology associated with the co-expressed receptor monomers and homomers. The Receptor-Heteromer Investigation Technology (Receptor-HIT) successfully employs a proximity-based reporter system, such as bioluminescence resonance energy transfer (BRET), in a configuration that enables determination of such heteromer-specific pharmacology. Therefore, Receptor-HIT provides a simple, robust and versatile approach for investigating the elusive ‘biochemical fingerprint’ of receptor heteromers.